Surface modification of decellularized trachea matrix with collagen and laser micropore technique to promote cartilage regeneration - Xu, Yong (Am J Transl Res, 2019)
The repair of long-segment tracheal defects remains a significant clinical challenge, to which, optimal biologically functioning tracheal alternatives may serve as a solution. Tissue-engineered trachea, regenerated from a decellularized trachea matrix using the laser micropore technique (LDTM), demonstrates the possibility of developing optimal tracheal substitutes, which retain the original tubular shape and adequate cartilage regeneration ability of trachea. However, the strict requirement with respect to the implantation cell density restricts the clinical translation of the LDTM, which has a low cell adherence rate. To overcome this problem, we propose a novel strategy involving collagen to modify the LDTM surface in order to enhance cell retention efficiency and promote homogeneous tracheal cartilage regeneration. The current results show that the modified LDTM significantly improves cell-seeding efficiency; moreover, it achieved stable cell retention and homogenous cell distribution. Additionally, at a relatively low implantation cell density (5.0 × 10(7) cells/mL, which is one-fourth of the cell-seeding density used in our previous study), homogeneous tubular cartilage was regenerated successfully both in vitro and in vivo. The cartilage had an exact tracheal shape, sufficient mechanical strength, typical lacuna structure, and cartilage-specific extracellular matrix deposition. Most importantly, the modified LDTM promoted chondrogenesis of the bone marrow-derived stem cells and the formation of homogeneous neocartilage in vivo. The current study has established a versatile and efficient cell-seeding strategy for the regeneration of multiple tissues. It also describes a technique for developing an optimal tracheal alternative for the repair and functional reconstruction of long-segment tracheal defects.